Study on the gas performance of ceramic membrane from kaolin prepared by phase inversion technique - Hubadillah, Siti Khadijah (2015)
Membrane for gas application have been widely used. Apart from that, ceramic membrane is gaining much attention towards separation technology due to its characteristics of offering high mechanical strength, chemical resistivity and thermal compatibility. However, production of ceramic membrane for gas separation in term of cost and energy reduce still remains as challenge until now, therefore this work addressed to the development of ceramic membrane from kaolin via simple phase inversion technique. First, ceramic membrane suspension have been prepared by stirring kaolin as raw material, N-methyl-2-pyrollidone (NMP) as solvent and polyethersulfone (PESf) as binder. Phase inversion tchnique conducted by casted the suspension on the glass plate with casting knife. In order to achieve the aims of this study, the development of ceramic membrane from kaolin were conducted into two objectives: (1) effect of particles sizes and, (2) effect of non-solvent coagulant bath. The types of kaolin particle sizes devoted as Type A kaolin (0.4-0.6µm) and Type B kaolin (10-15µm) whereas for different types of non-solvent were distilled water, ethanol and mixture of 70% NMP and 30% distilled water. Overall analysis showed that both effect of particle size and different caogulant generated different structure, properties and characteristic of membrane at two different composition. Polymer phase inversion is dominated at kaolin content of 24 to 34wt.% that caused the formation of finger-like voids of the phase inversed structure with Type A kaolin and strong caogulant of distilled water. An opposed condition was shown at highest kaolin content of 39 wt.% for both parameter that can be correlated to the viscous fingering mechanism in the formation of ceramic membrane structure. A slightly similar results trends and pattern was demostrated with Type B kaolin and weakest coagulant (mixture of 70% NMP and 30% distilled water). Overall performance showed that membrane with Type A kaolin and immersed into ethanol as coagulant at kaolin content of 39 wt.% showed the highest rejection (5.49 and 5.82 for CO2/N2 and O2/N2, respectively).